#### Answer

$A = 62.8^{\circ}$ which is $62^{\circ}48'$
$B = 27.2^{\circ}$ which is $27^{\circ}12'$
$c = 85.9 ~yd$

#### Work Step by Step

We can use the Pythagorean theorem to find c:
$c^2 = a^2+b^2$
$c = \sqrt{a^2+b^2}$
$c = \sqrt{(76.4~yd)^2+(39.3~yd)^2}$
$c = 85.9~yd$
We can use $a$ and $b$ to find angle A:
$tan~A = \frac{a}{b}$
$tan~A = \frac{76.4}{39.3}$
$A = tan^{-1}(\frac{76.4}{39.3})$
$A = 62.8^{\circ}$ which is $62^{\circ}48'$
We can use angle A and angle C to find angle B:
$B = 180^{\circ}-90^{\circ}-62.8^{\circ} = 27.2^{\circ}$
$B = 27.2^{\circ}$ which is $27^{\circ}12'$